OPTIMIZATION OF LINGZHI MUSHROOM (GANODERMA LUCIDUM) MEDIA USING OIL PALM WASTE FOR FUNCTIONAL FOOD - Kadir, Muh Ichwan; Nursaman, Herman; Sultan, Dian Mirnawaty (Universitas Gorontalo, 2026)
Oil palm stem waste is an environmental problem that holds great potential as an alternative substrate for mushroom cultivation due to its high lignocellulose content. Its utilization can replace the increasingly scarce sawdust while supporting the concept of a green economy. This study aimed to formulate a cultivation medium for Ganoderma lucidum based on oil palm stem waste through fermentation optimization using EM4 and molasses, to produce an eco-friendly medium that supports mushroom growth and functional food development. The research methods included substrate characterization (C/N ratio, lignin, phenol, moisture), fermentation optimization using Response Surface Methodology (RSM) with variations of EM4 dosage (1–5%), molasses concentration (5–15%), and fermentation duration (7–21 days). The optimized fermented substrate was then formulated into Baqlog medium (75% fermented substrate, 20% rice bran, 3% agricultural lime). Growth performance of G. lucidum was tested on Baqlog medium, followed by phytochemical analysis. The results showed that the optimal fermentation condition was at 3% EM4, 10% molasses, and 14 days, reducing lignin from 28.5% to 14.8%, phenol from 1.6% to 0.45%, and improving the C/N ratio from 44.2 to 28.5. Mycelial colonization was faster (18 days) compared to the control (34 days), with higher biomass (7.2 g/baglog, increased by 36%). Phenolic content also increased from 0.7 mg/g to 2.5 mg/g. In conclusion, fermentation of oil palm stem waste produced an effective medium that accelerated colonization, increased biomass, and enriched the bioactive content of G. lucidum.